EFEKTIVITAS PENGGUNAAN MEDIA WORDWAAL UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATERI KEKAYAAN BUDAYA INDONESIA (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
ABSTRACT The Effectiveness of Using Wordwall Media to Improve Student Learning Outcomes on the Material of Indonesian Cultural Wealth. This study aims to examine whether there is an effectiveness of the application of Wordwall media on learning outcomes on the material of Indonesian Cultural Wealth in class IV of Tarikolot 04 State Elementary School, Bogor Regency in the 2024/2025 academic year. The results of this study indicate that there is an effectiveness of using wordwall media on learning outcomes on Indonesian Cultural Wealth Material. This can be seen from the average value of N-Gain in the experimental class of 79, while the average value of N-Gain in the control class is 71.5. The completeness of learning outcomes obtained by the experimental class group was 82.5% while the control class was 70%. As well as the results of hypothesis testing that H0 is rejected and Ha is accepted because t-count (5,03356) > t-table (1.99085). From the results of the study it can be concluded that the use of Wordwall media is effective on the learning outcomes of Indonesian Cultural Wealth Material. The results of this study are expected to provide new knowledge about the use of Wordwall media to improve learning outcomes.